2018
DOI: 10.1111/jph.12755
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Pratylenchus brachyurus in soya bean crops

Abstract: The aim of the current study was to assess the activity of Purpureocillium lilacinum and Trichoderma harzianum fungi, either alone or in combination, and the use of a bioactivator to control Pratylenchus brachyurus in soya bean crops. Thus, two experiments were conducted in a greenhouse, and two were conducted in naturally infested fields. Both fungi were efficient in controlling the nematode when they were applied alone, whereas the combination of the two did not improve nematode control. However, the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…The susceptibility of soybean genotypes to M. arenaria and M. morocciensis is an important indication of the need for other control measures for this plant parasite, since these species are widespread in cultivated areas. Although several management strategies are applied to increase crop yield, none have been fully effective in keeping populations below the level of economic loss (DIAS-ARIEIRA et al 2018). Research on genetic resistance is important from the perspective of controlling plant-parasitic nematodes since the responses to these pathogens are reproduced in these hosts.…”
Section: Resultsmentioning
confidence: 99%
“…The susceptibility of soybean genotypes to M. arenaria and M. morocciensis is an important indication of the need for other control measures for this plant parasite, since these species are widespread in cultivated areas. Although several management strategies are applied to increase crop yield, none have been fully effective in keeping populations below the level of economic loss (DIAS-ARIEIRA et al 2018). Research on genetic resistance is important from the perspective of controlling plant-parasitic nematodes since the responses to these pathogens are reproduced in these hosts.…”
Section: Resultsmentioning
confidence: 99%
“…These species can endophytically associate with plants, colonize the root tissues, mainly the rhizoplane, and help managing nematodes in different ways, namely, by producing toxic substances that compromise the nematode development or the location of the host, by promoting plant growth and by activating defense mechanisms in plants (Machado et al, 2012;Xiang et al, 2017). Besides bacteria, fungi such as Pochonia chlamydosporia (Goddard) Zare and Gams and Purpureocillium lilacinum (Thom) Luangsa-ard et al have also been studied as important agents in the biological control of nematodes, acting in the reduction of juveniles and eggs (Silva et al, 2017;Dias-Arieira et al, 2018). In addition, fungi belonging to genus Trichoderma can reduce the number of nematodes through different action mechanisms such as direct parasitism, changes in the rhizosphere, enzyme activity and plant-resistance induction (Izuogu and Abiri, 2015;Zhang et al, 2015;Kath et al, 2017)…”
mentioning
confidence: 99%
“…In protected environment conditions, Dias-Arieira et al (2018) observed the effect of T. harzianum and P. lilacinum in the reduction of populations of P. brachyurus in soybean, where these fungi were potentiated when used together with an organomineral fertilizer. In the same study, the authors saw that the use of P. lilacinum + T. harzianum can reduce the number of P. brachyurus per 10 g of root by up to 61.2% in soy at 40 DAS and 47.2% at 60 DAS, under field conditions.…”
Section: Resultsmentioning
confidence: 99%